2021
DOI: 10.1186/s40360-021-00510-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring cardioprotective potential of esculetin against isoproterenol induced myocardial toxicity in rats: in vivo and in vitro evidence

Abstract: Background Esculetin is a natural coumarin derivative from various plants with multiple pharmacological effects. Hence, the present study was undertaken to explore the cardio protective potential of esculetin against isoproterenol induced myocardial toxicity in rats. Methods The treatment schedule was fixed for 28 days and the rats were divided into five groups of six each. Rats of group I received the normal saline and served as normal control, gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Oerlemans et al demonstrated that RIPK1, RIPK3, and mixed lineage kinase domain-like (MLKL) expression was up-regulated in the myocardium after reperfusion, and the necrosis inhibitor Necrostatin-1 could reduce the phosphorylation levels of RIPK1 and RIPK3 and the recruitment of MLKL, thus inhibiting cell necrosis and reducing myocardial infarct size (Oerlemans et al, 2012). Currently, I/R models are preferred to elucidate the effect of different factors on cardiomyocyte necrosis through various pathways such as mechanistic target of rapamycin (mTOR), rate-oxygenation (ROX) and MLKL (Supplementary Table S2) (Yang et al, 2018a;She et al, 2019;Chen et al, 2020;Jiang et al, 2021c;Han et al, 2021;Liu et al, 2021;Pullaiah et al, 2021;Zhang et al, 2021).…”
Section: Necrosis Pathways In Cardiovascular Diseasesmentioning
confidence: 99%
“…Oerlemans et al demonstrated that RIPK1, RIPK3, and mixed lineage kinase domain-like (MLKL) expression was up-regulated in the myocardium after reperfusion, and the necrosis inhibitor Necrostatin-1 could reduce the phosphorylation levels of RIPK1 and RIPK3 and the recruitment of MLKL, thus inhibiting cell necrosis and reducing myocardial infarct size (Oerlemans et al, 2012). Currently, I/R models are preferred to elucidate the effect of different factors on cardiomyocyte necrosis through various pathways such as mechanistic target of rapamycin (mTOR), rate-oxygenation (ROX) and MLKL (Supplementary Table S2) (Yang et al, 2018a;She et al, 2019;Chen et al, 2020;Jiang et al, 2021c;Han et al, 2021;Liu et al, 2021;Pullaiah et al, 2021;Zhang et al, 2021).…”
Section: Necrosis Pathways In Cardiovascular Diseasesmentioning
confidence: 99%
“…2 The blockage of the coronary artery inflammation, hyperlipidemia, and depletion of plasma membrane integrity. 3 The inflammatory condition during the development of MI comprises higher pro-inflammatory cytokine expressions. TNF-α is a foremost inflammatory regulator, which stimulates the expression of other inflammatory cytokines and chemokines.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of MI comprises oxidative stress, inflammation, hyperlipidemia, and depletion of plasma membrane integrity. 3…”
Section: Introductionmentioning
confidence: 99%
“…Further, esculetin attenuated alterations in Ang-II and acetylcholine-mediated vascular reactivity [21]. A recent preclinical study reported that esculetin shows cardioprotective effects against isoproterenol-induced myocardial infarction and myocardial membrane stabilization [22]. However, the efficacy of esculetin is compromised due to its limited bio-availability due to which, it has to be administered at higher doses to mitigate mitochondrial-derived oxidative stress.…”
Section: Introductionmentioning
confidence: 99%